KONTRIBUSI PENDAPATAN DAN CURAHAN WAKTU KERJA ISTRI PEMBUDIDAYA RUMPUT LAUT TERHADAP PENINGKATAN PENDAPATAN RUMAH TANGGA - Astylia Abuk Bria; Sunadji Sunadji; Yulianus Linggi (Jurnal Akuatik, 2022)
This research was conducted in West Kupang District, Kupang Regency, East Nusa Tenggara Province in October-November 2020. The aim of the study was (1) to determine the average contribution of the seaweed cultivator's wife's income to household income in order to determine the role of income. seaweed cultivator wife on household improvement. (2) to determine the average amount of time spent working for the social activities of the wives of seaweed cultivators, both formal and non-formal. The population in this study is the wife of seaweed cultivators who work as seaweed workers who live in West Kupang District, Kupang Regency, while the samples taken proportionately from each of the existing villages, where the number of samples is 60 respondents spread across three villages namely Bolok, Tesabela and Tablolong. And to determine the respondent (sample) from each village using accidental sampling method, where the sample taken is based on the population found with the consideration that the population distribution is not even in each village. And the data sources used are primary data and secondary data. The data analysis used is descriptive quantitative, namely the discussion of the variables of the wife's role in increasing household income. Quantitative analysis is using the analysis of income contributions. The results of this study indicate that the activities carried out by the wife in the process of cultivating seaweed in helping to increase household income are processing seaweed for sale with the highest number or at most 37 people or with a presentation value of 61.67% while the lowest or a little with a total income of one million to one million and five hundred with a presentation value of 20% with the number of respondents 12 people. The average contribution of the wife's income to the household income of seaweed cultivators is 37%, which is in the sufficient category. Keywords: Contribution of income, Spending of wife's working time, household inco